Analisis Pengaruh Produktivitas Tenaga Kerja, Upah Minimum, Dan Pertumbuhan Ekonomi Terhadap Penyerapan Tenaga Kerja(Di 35 Kabupaten/Kota Provinsi Jawa Tengah Padatahun 2010-2014) - Nurmaini, Muktiratih; , Drs. Triyono, M.Si (2016)
The amount of the unemployment rate in Central Java indicate that the level of employment in 35 districts/cities in Central Java Province is still low. Despite the economic pertembuhan in 35 districts/cities in Central Java is increasing every year but have not been able to absorb labor. The purpose of this research was to determine the effect of Labor Productivity, the Minimum Wages and Economic Growth on Absorption of Labour in 35 districts/cities in Central Java Province. This study uses quantitative data with methods Pooled Least Square (PLS), which consists of the data times series during the period 2010-2014 and cross section data 35 districts/cities in Central Java. The results of this study indicate that economic growth and no significant positive effect on employment, to the minimum wage and labor productivity negatively affect labor peyerapan. Directions negative regression coefficient indicates that an increase in the productivity of labor and the minimum wage reduces employment. And the direction of positive regression coefficient indicates that increased economic growth can lead to increased employment.